Chemical and microbiological quality of commercial fresh and frozen chicken drumstick in Umuhia, Nigeria - Judith Chukwuebinim Okolo; Jude Chukwuemeke Igborgbor; Unyimeabasi Effiong Anana; Gideon Ikechukwu Ogu (International Journal on Food, Agriculture and Natural Resources, 2022)
Chicken meat, an excellent source of good quality proteins, is highly susceptible to microbial contaminations and heavy metals from feeds, processing, and retailing environments, thereby posing health risks to consumers. Therefore, the proximate composition, heavy metal concentrations, and microbial loads of commercial fresh and frozen chicken drumsticks, randomly sourced from poultry farms and groceries, respectively, within Umuahia metropolis, Abia State, Nigeria, were investigated to ascertain their qualities. A total of 40 (20 each of the fresh and frozen) chicken drumstick samples were processed and analyzed for proximate (moisture, fats, ash, proteins, fibers, and carbohydrates), heavy metal (cadmium, chromium, copper, manganese, nickel, zinc, and lead) contents, and microbial loads (total viable counts, Escherichia coli counts, Salmonella counts, Staphylococcus counts and fungal counts) and characterization using standard techniques. Results were analyzed statistically (p<0.01, 0.05). The fresh chicken drumstick samples had significantly higher (p<0.01, 0.05) levels of moisture (61.38 ± 0.34 %), proteins (22.30 ± 0.02 %), ash (5.27 ± 0.17 %) and microbial contents (0.24 × 102 CFU/g to 2.42 × 104 CFU/g), when compared with the frozen drumstick samples with significantly higher (p<0.01, 0.05) contents of fats (3.70 ± 0.13 %), carbohydrates (12.55 ± 0.27 %) and heavy metals (0.047 ± 0.017 mg/kg to 0.852 ± 0.456 mg/kg). This suggests that fresh chicken drumstick is more nutritionally beneficial, provided they are thoroughly treated with heat before consumption to prevent foodborne diseases from bacterial and fungal contaminations. Although the levels of heavy metals in both meat samples are below the toxic limits, consumers should be wary of bioaccumulation and bio-magnification of heavy metals when constantly exposed to them. Hence, constant surveillance of chicken meat is encouraged to monitor their exposure levels to these chemicals and biohazards.